Contrôle de Gestion et Performance dans les Organisations Publiques Marocaines: Quelles Spécificités? - Botaina Mjidila; Youssef El Wazani; Malika Souaf (European Scientific Journal, ESJ, 2017)
This paper focuses on the practice of Management Control within public organizations. Also, it provides an overview of the various constraints limiting the success of the implementation of this discipline in this type of organization. It also focuses on the impact of the implementation of a performance management system on these structures. Modernization and performance, two notions which is interdependent with the practice of management control, will also be mentioned in a synthetic way. In order to do this, we first present the concepts of modernization and performance. This was done according to different approaches. After then, it analyzed the performance management tool mostly used by private companies: "the management dashboard". Finally, the last part of this study will be devoted to discussing the relevance of the balanced scorecard developed by Norton and Kaplan. Also, they considered the balance scorecard to be the most appropriate tool in the public domain.